Kinetics of L-ascorbic acid degradation and non-enzymatic browning development in hot-compressed water - Feng, Liang; Yang, Yan; Xie, Ya-ting; Liu, Shuang-shuang; Peng, Xuan; Hu, Sheng; Yu, Ai-nong (Frontiers in Nutrition, 2023)
The effect of reaction conditions, which comprised the reaction temperature (150–190°C), processing time (0.50, 0.75, 1.00, 1.25, 1.50, 2.00, and 2.50 h), pH (5.0, 7.0, and 9.5), and concentration (0.03–0.07 mol/L) of L-ascorbic acid (ASA), on the degradation of ASA was investigated in hot-compressed water (HCW). The degradation kinetics of ASA and generation kinetics of browning products (BPs) were studied. The results showed that ASA degradation conformed to the pseudo-first-order kinetics, and the formation of BPs was closely related to the concentration of H3O+ in HCW. The acidic condition (pH = 5.0) and lower concentration of ASA (0.03 mol/L) were more favorable for ASA degradation. In HCW, the average apparent activation energy (Ea) of ASA was 15.77, 31.70, and 47.53 kJ/mol at pH 5.0, 7.0, and 9.5, respectively. The possible degradation mechanisms of ASA and the generation of BPs in HCW were proposed based on the experimental results.